Development of Islamic Character Education Model to Overcome Students Moral Decadence at MTSN 1 Bandar Lampung (International Journal of Education and Literature, 2025)
This study aims to describe the implementation of Islamic character education at MTsN 1 Bandar Lampung and analyze its role in overcoming students' moral decadence. It uses a qualitative descriptive approach with data collected through in-depth interviews with five respondents. The focus of the interviews was on five key aspects: the implementation of character education, the core values instilled, the effectiveness of the program, challenges faced, and suggestions for improvement. The study finds that Islamic character education at MTsN 1 Bandar Lampung is integrated through the habituation of worship, the application of Islamic values-based discipline, teacher examples, the integration of character education materials into the curriculum, and the support of counseling services. The five key character values emphasized are honesty, discipline, responsibility, social care, and politeness. The program is considered quite effective in reducing disciplinary violations and enhancing students' moral awareness. However, the program faces challenges, such as the influence of social media, peer pressure, limited learning time, and insufficient teacher training. These challenges hinder the full potential of the program, but despite these barriers, it has still managed to positively impact the students' moral development. The study concludes that Islamic character education can significantly contribute to addressing moral decadence among students, though continuous efforts to address challenges are necessary to further improve its impact.